2015
DOI: 10.11152/mu.2013.2066.174.csu
|View full text |Cite
|
Sign up to set email alerts
|

Contrast enhanced ultrasound for the diagnosis of liver hemangiomas – results of a Romanian multicentre study

Abstract: Background and aim: Contrast enhanced ultrasound (CEUS) has been proven to be a reliable method for the characterization of focal liver lesions (FLL). The aim of this paper was to evaluate the performance of CEUS for the diagnosis of liver hemangiomas in a large cohort of patients. Material and method: We performed a multicentre prospective study which included successive CEUS examinations from fourteen centers from Romania. CEUS examinations were performed in de novo FLL, using low mechanical index ultrasound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…On CEUS, the typical feature of liver hemangioma is peripheral nodular and centripetal enhancement during the arterial phase followed by hyper-or isoenhancement during the portal venous and late phases [4][5][6][7] . In contrast, the feature of liver metastases is complete or rim-like hyperenhancement during the arterial phase followed by hypoenhancement in the portal venous and late phase.…”
Section: Introductionmentioning
confidence: 99%
“…On CEUS, the typical feature of liver hemangioma is peripheral nodular and centripetal enhancement during the arterial phase followed by hyper-or isoenhancement during the portal venous and late phases [4][5][6][7] . In contrast, the feature of liver metastases is complete or rim-like hyperenhancement during the arterial phase followed by hypoenhancement in the portal venous and late phase.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the features of the lesion are atypical at conventional ultrasound (US), further investigation is required. Contrast-enhanced ultrasound (CEUS) has been proven to be a reliable method for the characterization of the focal liver lesions [ 5 , 6 ], it is a sensitive and very specific method for the diagnosis of hemangiomas [ 7 ]. Based on the guidelines [ 8 ] and clinical experience, the typical CEUS features of hepatic hemangioma were peripheral nodular enhancement or circular enhancement in the arterial phase with centripedal filling, hyperechoic/ isoechoic change in the portal venous phase and late phase.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound without contrast in most cases is not a reliable examination for focal liver lesions with the exception of simple liver cysts. A few years ago, the only other imaging methods were CT and MRI with contrast and Technetium-99m labeled studies [2]. In the study by Sirli et al involving 1153 patients with FLL, 238 cases of hemangioma were found using CEUS, and only 11 of them were misdiagnosed.…”
Section: Role Of Ceus In the Diagnosis Of Hemangiomamentioning
confidence: 99%
“…In contrast, focal fatty infiltrations of the liver can be seen in everyday practice [1]. Traditional ultrasound is not enough to diagnose focal liver lesions, except for cystic liver lesions, some hydatid cysts, and fatty liver lesions [2]. Contrast-enhanced ultrasound (CEUS), on the other hand, which is performed with sulfur hexafluoride microbubbles, is a real-time diagnostic method that helps make a reliable diagnosis for different liver lesions, based on contrast enhancement during arterial phase portal venous and late (sinusoidal) phase [3].…”
Section: Introductionmentioning
confidence: 99%